Expression of CMIP in podocytes is restricted to specific classes of lupus nephritis - Bouachi, Khedidja (PLoS One, 2018)
Lupus glomerulopathies are classified into various histological patterns, which probably result from different pathophysiological origins. Podocyte injury can be demonstrated in lupus nephritis but its clinical relevance is far little appreciated and is often masked by proliferative lesions and inflammatory cell infiltrations. Two patterns of podocyte lesions may be considered, either occurring in the context of renal inflammation or reflecting podocyte dysfunction in non-proliferative and non-inflammatory glomerulopathies. This distinction remains elusive since no reliable biomarker discriminates between both entities. CMIP was recently found induced in some glomerular disease but its expression in different lupus nephritis classes has not been investigated. Twenty-four adult patients with lupus nephritis, including non-proliferative (n = 11) and proliferative (n = 13) glomerulopathies were analyzed. Clinical, biological and immunological data were compared with immunomorphological findings. We analyzed by quantitative and qualitative methods the expression of CMIP in different histological classes. We found CMIP abundance selectively increased in podocytes in class II and class V glomerulopathies, while in proliferative forms (class III and class IV), CMIP was rarely detected. CMIP was not expressed in cellular crescents, endothelial cells or mesangial cells. CMIP colocalized with some subsets of B and T cells within glomerular or interstitial mononuclear cell infiltrates but never with macrophages. Hematuria is rarely present in lupus glomerulopathies expressing CMIP. There was no correlation between classical immunological markers and CMIP expression. Thus, CMIP induction in lupus nephritis seems restricted to non-proliferative glomerulopathies and may define a specific pattern of podocyte injury.